Development of a cost effective medium for enhanced production of Bacillus thuringiensis δ-endotoxin - Bhowmik, Anamika (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.